Natural monoacetylenes studied by quantum-chemical chemistry. Issue 3 (2010) - Roman, Maciej; Baranska, Malgorzata
Abstract : This study is a part of the project focused on the vibrational analysis of natural mono- and polyacetylenes by using Raman spectroscopy and theoretical calculations. Their vibrational spectra show strong and polarized –C≡C– bands in the region of about 2200 cm –1 . Mono- as well as polyacetylenes are supposed to be active in plants yet not available in an isolated form, so theoretical simulation of their vibrational spectra and comparison with the registered ones seems to be an excellent way to confirm or exclude the presence of these compounds in the investigated plants. Such an approach was applied here to analyze polyacetylenes in roots of Coreopsis grandiflora . According to literature, this plant should contain a monoacetylene substituted by a thiophene ring. Theoretical calculations allowed to confirm this assumption.